2005
DOI: 10.1038/sj.bjp.0706326
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological characterization of nucleotide P2Y receptors on endothelial cells of the mouse aorta

Abstract: 1 Nucleotides regulate various effects including vascular tone. This study was aimed to characterize P2Y receptors on endothelial cells of the aorta of C57BL6 mice. Five adjacent segments (width 2 mm) of the thoracic aorta were mounted in organ baths to measure isometric force development. -methyladenosine3 0 ,5 0 -bisphosphate (MRS2179) inhibited ADP-evoked relaxation only. 8 Taken together, these results point to the presence of functional P2Y 1 (ADP), P2Y 2 (ATP, UTP) and P2Y 6 (UDP) receptors on murine aor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(88 citation statements)
references
References 34 publications
4
83
1
Order By: Relevance
“…2 This receptor has been shown to contribute to endothelium-dependent relaxation through nitric oxide and prostacyclin release. 16,17,34 However, the function of the P2Y 1 receptor in endothelial cells is largely unknown. Several findings indicate that adenine nucleotides may contribute to an inflammatory state of the endothelium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 This receptor has been shown to contribute to endothelium-dependent relaxation through nitric oxide and prostacyclin release. 16,17,34 However, the function of the P2Y 1 receptor in endothelial cells is largely unknown. Several findings indicate that adenine nucleotides may contribute to an inflammatory state of the endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…9,[12][13][14] Hence, this receptor could represent an interesting target for new antiplatelet compounds. 7,15 The endothelial P2Y 1 receptor contributes, like other P2 receptor subtypes, to nucleotide-induced relaxation 16,17 and was recently shown also to be involved in human endothelial cell migration. 18 The role of P2Y 1 in leukocytes is less well established.…”
Section: Clinical Perspective P 763mentioning
confidence: 99%
“…Well before cloning any of the purinergic or nucleotide receptors, Van Coevorden and Boeynaems showed that micromolar concentrations of ADP stimulated the release of prostaglandin (PG)I 2 from cultured bovine aortic endothelial cells. 19 Recently, it has been reported that ADP induces endothelium-dependent relaxation of several arteries, including rat mesenteric artery, 20 guinea pig, and mouse aorta 21,22 via NO release. These studies suggested that ADP could exert 2 opposite actions on platelet aggregation in vivo: a direct stimulation and an indirect inhibition mediated by PGI 2 and NO released from the endothelium.…”
Section: Shen and Dicorleto Adp Signaling And Endothelial Cell Migratmentioning
confidence: 99%
“…[19] Adenosine diphosphate has been shown to induce vasoconstriction via P2Y12 receptors; however, it is also believed to cause arterial relaxation by increasing the synthesis of endothelium-derived nitric oxide (NO). [19][20][21] Thus, the effect of ADP-mediated pathways on the endothelium is currently unclear. [22] Clopidogrel has been reported to exhibit vasomodulatory activity [23] and direct endothelial effects independent from antiplatelet actions, [24] which are still not fully understood.…”
Section: Discussionmentioning
confidence: 99%